Does insufficient sleep affect how you learn from reward or punishment? Reinforcement learning after 2 nights of sleep restriction. (20th November 2020) - Gerhardsson, Andreas; Porada, Danja K.; Lundström, Johan N.; Axelsson, John; Schwarz, Johanna
Abstract: To learn from feedback (trial and error) is essential for all species. Insufficient sleep has been found to reduce the sensitivity to feedback as well as increase reward sensitivity. To determine whether insufficient sleep alters learning from positive and negative feedback, healthy participants ( n  = 32, mean age 29.0 years, 18 women) were tested once after normal sleep (8 hr time in bed for 2 nights) and once after 2 nights of sleep restriction (4 hr/night) on a probabilistic selection task where learning behaviour was evaluated in three ways: as generalised learning, short‐term win–stay/lose–shift learning strategies, and trial‐by‐trial learning rate. Sleep restriction did not alter the sensitivity to either positive or negative feedback on generalised learning. Also, short‐term win–stay/lose–shift strategies were not affected by sleep restriction. Similarly, results from computational models that assess the trial‐by‐trial update of stimuli value demonstrated no difference between sleep conditions after the first block. However, a slower learning rate from negative feedback when evaluating all learning blocks was found after sleep restriction. Despite a marked increase in sleepiness and slowed learning rate for negative feedback, sleep restriction did not appear to alter strategies and generalisation of learning from positive or negative feedback.